Measurement of Sound Speed Using a Frequency Generator-assisted Resonance Tube for STEM-based Learning - Nurpratiwi, Febrianty; Hernani, Hernani; Prima, Eka Cahya; Septiyanto, Arifin (Jurnal Pendidikan Matematika dan Sains, 2025)
This study investigates the measurement of the speed of sound in air using a resonance tube assisted by a smartphone-based frequency generator, designed to support STEM-based learning. The experiment follows a quantitative approach, with the length of the air column as the independent variable and the speed of sound as the dependent variable. Control frequencies of 495 Hz, 755 Hz, 1010 Hz, 1270 Hz, and 1530 Hz were generated via a mobile application. Resonance points were identified by observing the peak sound intensity using a digital sound level meter, which indicated the formation of standing waves. The results showed a strong linear relationship between wavelength (λ) and wave period (T), with regression equations λ = 347.62T + 0.0098 (open pipe) and λ = 361.59T − 0.0176 (closed pipe), each with a correlation coefficient of R = 0.99. At room temperature (24.4°C), the measured speed of sound was (347.6 ± 0.2) m/s for the open pipe and (361.6 ± 0.1) m/s for the closed pipe. These results demonstrate that low-cost, smartphone-assisted setups can produce accurate, reliable data. This method enhances student engagement and understanding of acoustic phenomena, providing an accessible and effective model for implementing hands-on STEM-based learning in physics education.